Ulahahan Babatu Orchestra: Concept and Functional Role of Inclusive Music Community - Aryandari, Citra; Siahaya, Karel Martinus; Hazmi, Fariz Al (Harmonia: Journal of Arts Research and Education, 2023)
The presence of Toki Batu music in Ulahahan Village as a cultural product cannot be separated from the musical narrative of the Maluku people, which has been part of social and cultural life since ancient times. This study aims to explain the concept of inclusiveness within the group and its functional role in society as an inclusive music community. The research method uses a descriptive qualitative with an ethnographic approach. Data collection techniques were carried out through observation, semi-structured interviews, and documentation. The study results explain that the concept of inclusiveness in the Ulahahan Babatu Orchestra community lies in membership open to people from various backgrounds, both children and adults. The Community also does not provide special requirements to be able to join the group because Toki Batu’s music belongs to the Community, and anyone should be able to contribute. The leadership style used is based on local culture by adopting respect for elders. As a result, the leader is someone who is older and more experienced in community management rather than someone who has mastered music. Functionally the role of the Toki Batu music community revives community creativity and influences collectively in various fields such as recreational, educational, communication and religious facilities.